Analisis Kesulitan Belajar Asam Basa pada Siswa Kelas XII SMAN 1 Masbagik - Farizal, Reza; Haris, Mukhtar; Hadisaputra, Saprizal (FKIP University of Mataram, 2024)
This study aims to determine the form of learning difficulties and describe the factors that cause learning difficulties of grade XII students of SMAN 1 Masbagik on acid-base material. The research method used was qualitative descriptive with a population of 102 students from classes XII F3, XII F4, and XII F5. The research sample was taken using a saturated sampling method, and data was collected through test questions and questionnaires. The results showed that; 1) The level of difficulty of learning acid-base students in mastery of concepts by 58% in the category is quite difficult, linking relationships between concepts by 67% in the difficult category and applying formulas for solving problems by 80% in the difficult category. 2) The level of learning difficulty of students due to internal factors is mostly (47%) in the very low category. The level of student learning difficulty is due to the aspect of interest with the highest percentage of 70% in the low category, because the motivation aspect with the highest percentage of 53% in the category is quite high, and because the health aspect with the highest percentage of 56% in the category is very low. 3) The level of learning difficulty of students due to external factors is mostly (70%) in the low category. The level of learning difficulty of students is due to the school aspect with the highest percentage of 51% in the low category, because of the material aspect with the highest percentage of 56% in the low category, because of the family aspect with the highest percentage of 48% in the low category, and because of the community aspect with the highest percentage of 43% in the very high category.